2009
DOI: 10.1271/bbb.90502
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Expression Analysis of the Exopolysaccharide Gene Cluster inLactobacillus fermentumTDS030603

Abstract: Part of the exopolysaccharide gene cluster of Lactobacillus fermentum TDS030603 was characterized. It consists of 11,890 base pairs and is located in the chromosomal DNA, 13 open reading frames of which were encoded. Out of the 13 open reading frames, six were found to be involved in exopolysaccharide synthesis; however, five were similar to transposase genes of other lactobacilli, and two were functionally unrelated. Expression analysis revealed that the exopolysaccharide synthesis-related genes were expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The GTs connects the EPS repeating unit by serial transfer of nucleotide sugar residues onto a lipid carrier or onto a growing chain. Finally, encompasses genes involved in transport and polymerization [28,30,33]. Many gene structures for EPSs synthesis from various LAB have been isolated and identified, e.g., Streptococcus thermophilus, Streptococcus macedonicus, Lactococcus lactis subsp.…”
Section: Genetics Of Exopolysaccharides Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GTs connects the EPS repeating unit by serial transfer of nucleotide sugar residues onto a lipid carrier or onto a growing chain. Finally, encompasses genes involved in transport and polymerization [28,30,33]. Many gene structures for EPSs synthesis from various LAB have been isolated and identified, e.g., Streptococcus thermophilus, Streptococcus macedonicus, Lactococcus lactis subsp.…”
Section: Genetics Of Exopolysaccharides Productionmentioning
confidence: 99%
“…bulgaricus but the understanding on exact mechanisms at genomic level, e.g., assembly of repeating units or regulatory mechanisms of EPSs yield is still limited [9]. These LAB strains contain a number of glycosyl transferases in the EPSs gene cluster, which provide many chemical structures of the repeating unit, and hence their EPSs have wide diversity of physicochemical properties [33]. Also, several primer pairs have already been described, such as primers targeting regulatory genes, genes involved in chain length determination and genes coding for glycosyl transferases [34].…”
Section: Genetics Of Exopolysaccharides Productionmentioning
confidence: 99%
“…The strain can metabolize several carbohydrates, and the maximum EPS production (69 mg/l) was achieved when glucose was used as the sole carbon source. Another study revealed that EPS-related genes of the strain form a cluster in the genome [13]. Their nucleotide sequences were partially revealed; however, there is so far no information about the relationship between EPS production and EPS-related gene expression levels.…”
mentioning
confidence: 99%
“…The genes which encode the proteins or enzyme required for the biosynthesis of EPS are located on chromosomes in those which are thermopiles (Yildiz et al 2015 ) and on plasmid in most lactic acid bacteria (Laws et al 2001 ). In contrast, a lack of plasmids encoding components required for slime production was observed for thermophilic LAB Streptococcus thermophilus (Harutoshi 2013 ) and a location of the EPS gene cluster in chromosomal DNA was reported for Lactobacillus fermentum TDS030603 (Dan et al 2009 ).…”
Section: Specifi C Conditions For Eps Synthesis By Thermophilesmentioning
confidence: 99%